Development and Implementation of Information Technology-Based Learning Media in Project-Based Animation Learning at State Vocational School 4 Madiun - Isna Qurrotun Aini; Novi Leny Rahmadhani; Farel Ramadani; Adelia Sherlyna; Narelia Rizky Oktadivani; Muhammad Akmal Bahauddin (Universitas Negeri Surabaya, 2026)
The transformation of education in the digital era necessitates the integration of information technology into learning processes to enhance the quality and relevance of education, particularly in vocational education. This study aims to analyze the development and implementation of information technology-based instructional media in project-based animation learning at SMK Negeri 4 Madiun. The study employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation and were subsequently analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings reveal that information technology-based instructional media have been adaptively implemented and effectively integrated with industry demands through the Project-Based Learning (PjBL) model. Digital technologies function as the primary instructional medium throughout the learning process, ranging from concept visualization to animation production, and are supported by project-based assessment involving industry practitioners. The implementation of these technologies has contributed to increased student engagement, creativity, and technical competencies relevant to workplace requirements. However, several challenges were identified, including limitations in facilities and infrastructure, particularly the availability of devices with adequate specifications, as well as constraints related to instructional time and students’ digital competencies.